Investigating discourse markers “you know” and “I mean” in mediatized English political interviews: a corpus-based comparative study - Fu, Yanli; Afzaal, Muhammad; El-Dakhs, Dina Abdel Salam (Frontiers in Communication, 2024)
This study employs a corpus-based approach to examine and compare the use of two discourse markers (DMs), “you know” and “I mean”, within the context of two mediatised English political interviews. The analysis encompasses frequencies, functions, co-occurrences, and positional distributions of these DMs. The study utilizes specialized corpora from two political interview programs: CGTN’s The Point with Liu Xin and BBC’s HARDtalk. The frequency analysis reveals that “you know” is statistically more prevalent than “I mean” in both programs, reflecting the spontaneity, interactivity, and need for clarification characteristic of political interviews. Notably, the Chinese interviewer (IR) uses “you know” more extensively, possibly due to a cultural preference for ensuring mutual understanding and engaging the audience, while the British IR employs “I mean” slightly more frequently, likely reflecting a tendency to clarify or reframe statements for precision. Functionally, these DMs serve diverse purposes such as hedging, agreeing, and monitoring across various domains including interpersonal, sequential, and rhetorical. Positional analysis shows “you know” typically appearing medially and “I mean” often in initial positions. These results underscore the distinctive interviewing styles of the two IRs and the pivotal role of these DMs in fulfilling a spectrum of communicative functions. This research offers valuable insights into the interviewer’s perspective in political interviews.